A compliant, self-adhesive and self-healing wearable hydrogel as epidermal strain sensor. Issue 15 (29th March 2018) - Liu, Shuqi; Zheng, Rongmin; Chen, Song; Wu, Yunhui; Liu, Haizhou; Wang, Pingping; Deng, Zhifu; Liu, Lan
Abstract : A compliant, self-adhesive and self-healing epidermal strain sensor that shows excellent sensing performance at ultra-low and high strain. Abstract : With the ability to switch transform the mechanical stimuli of epidermal deformations to electrical signals, epidermal strain sensors can be widely applied to monitor physiological signals, detect body movements and control robots. Epidermal strain sensors are required to conform to the human body under complex motions typically from tiny epidermal deformations (<1% strain) to large body movements (10–75% strain). In this study, a compliant, self-adhesive and self-healing epidermal strain sensor was fabricated with the addition of polydopamine into polyvinyl alcohol hydrogel. Due to the compliant and self-adhesive characteristics, the as-prepared strain sensors can fix well onto the epidermis without adhesive tape, perceiving extremely gentle deformations (0.1% strain), such as pulse beats, vibration of the throat, and facial expression changes. This highly stretchable strain sensor can also monitor the large motions (up to 500% strain) of legs and fingers. Moreover, owing to the reversible boron ester bond, the hydrogel has super self-healablity (self-healed in 250 ms at ambient temperature, 25 °C), which makes our sensors more humanoid. At last, thanks to its excellent ability to detect a large range of strains, the self-healing epidermal strain sensor is effective in monitoring physiological signals and body movements.